Fathers' Needs and Masculinity Dilemmas in a Neonatal Intensive Care Unit in Denmark - Noergaard, Betty (Adv Neonatal Care, 2017)
BACKGROUND: Most healthcare professionals in neonatal intensive care units typically focus on the infants and mothers; fathers often feel powerless and find it difficult to establish a father-child relationship. In family-centered healthcare settings, exploring fathers' experiences and needs is important because men's roles in society, especially as fathers, are changing. PURPOSE: To describe fathers' needs when their infants are admitted to a neonatal intensive care unit and to discuss these needs within a theoretical framework of masculinity to advance understanding and generate meaningful knowledge for clinical practices. METHODS: This qualitative study used participant observation, interviews, multiple sequential interviews, and a focus group discussion. Data were analyzed using grounded theory principles. RESULTS: Analysis of the fathers' needs generated 2 primary themes: (1) Fathers as caregivers and breadwinners and (2) fathers and emotions. Fathers wished to be involved and to take care of their infants but have to balance cultural and social norms and expectations of being breadwinners with their wishes to be equal coparents. IMPLICATIONS FOR PRACTICE/RESEARCH: Health professionals in neonatal intensive care units must be aware of fathers' need and desire to be equal coparents. Nurses should play a key role by, for example, showing that fathers are as important to their infants as are the mothers, helping them become involved in childcare, and ensuring that they are directly informed about their children's progress. Further research in other cultural settings would contribute to knowledge regarding fatherhood and the role of fathers in childcare.